THE NAPPE STRUCTURE OF THE TECTONIC WINDOW OF DOLIANA (CENTRAL PELOPONNESUS, GREECE) - Lekkas, S.; Skourtsos, E. (Bulletin of the Geological Society of Greece, 2004)
In the tectonic window of Doliana (central Peloponnesus, Greece) a variety of geological formations occurs deriving from different sedimentation palaeoenvironments and characterized by different tectonometamorphic evolution. These rocks initially formed thrust nappes of great extension and thickness which stacked one over the other during the Lower Oligocene-Lower Miocene. The early compressing structures that were formed by the emplacement of the nappes were almost totally overprinted by the later-orogenic extension that affected the nappe-column in the Upper Miocene-Lower Pliocene. Its main tectonic characteristic was the formation of low-angle normal faults, which constitute the tectonic contacts of the nappes. These faults led to the exhumation of the formerly deeply buried metamorphic rocks that are forming the core of the tectonic window. Apart from these structures during the evolution of this deformation phase an intense thinning of the units of the upper plate took place, causing the upper units coming closer or next to the lower ones. After the Lower Pliocene a second extensional phase affected the already thinned nappe-column with the formation of high-angle normal faults.